Acute Hyperammonemic Encephalopathy in Adults: Imaging Findings - U-King-Im, J.M.; Yu, E.; Bartlett, E.; Soobrah, R.; Kucharczyk, W. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Acute hyperammonemic encephalopathy has significant morbidity and mortality unless promptly treated. We describe the MR imaging findings of acute hyperammonemic encephalopathy, which are not well-recognized in adult patients. MATERIALS AND METHODS: We retrospectively reviewed the clinical and imaging data and outcome of consecutive patients with documented hyperammonemic encephalopathy seen at our institution. All patients underwent cranial MR imaging at 1.5T. RESULTS: Four patients (2 women; mean age, 42 ± 13 years; range, 24–55 years) were included. Causes included acute fulminant hepatic failure, and sepsis with a background of chronic hepatic failure and post–heart-lung transplantation with various systemic complications. Plasma ammonia levels ranged from 55 to 168 μmol/L. Bilateral symmetric signal-intensity abnormalities, often with associated restricted diffusion involving the insular cortex and cingulate gyrus, were seen in all cases, with additional cortical involvement commonly seen elsewhere but much more variable and asymmetric. Involvement of the subcortical white matter was seen in 1 patient only. Another patient showed involvement of the basal ganglia, thalami, and midbrain. Two patients died (1 with fulminant cerebral edema), and 2 patients survived (1 neurologically intact and the other with significant intellectual impairment). CONCLUSIONS: The striking common imaging finding was symmetric involvement of the cingulate gyrus and insular cortex in all patients, with more variable and asymmetric additional cortical involvement. These specific imaging features should alert the radiologist to the possibility of acute hyperammonemic encephalopathy. ALTalanine transaminaseAPalkaline phosphataseASTaspartate transaminaseDWIdiffusion-weighted imagingEEGelectroencephalographyFLAIRfluid-attenuated inversion recoveryGCSGlasgow Coma ScaleICUintensive care unitIVintravenousN/Anot applicablePTprothrombin timeTPNtotal parenteral nutrition